Intergenerational Transmission of Maltreatment: A Multilevel Examination - Leve, Leslie D. (Dev Psychopathol, 2015)
Despite the commonly held belief that there is a high degree of intergenerational continuity in maltreatment, studies to date suggest a mixed pattern of findings. One reason for the variance in findings may be related to the measurement approach used, which includes a range of self-report and official indicators of maltreatment and both cross-sectional and longitudinal designs. This study attempted to shed light on the phenomenon of intergenerational continuity of maltreatment by examining multiple indicators of perpetration of maltreatment in young adults and multiple risk factors across different levels within an individual’s social ecology. The sample included 166 women who had been placed in out-of-home care as adolescents (>85% had a substantiated maltreatment incident) and followed into young adulthood, and included three waves of adolescent data and six waves of young adult data collected across 10 years. The participants were originally recruited during adolescence as part of a randomized controlled trial examining the efficacy of the Treatment Foster Care Oregon intervention. Analyses revealed weak to modest associations between the three indicators of perpetration of maltreatment in young adulthood, i.e., official child welfare records, self-reported child welfare system involvement, and self-reported maltreatment (r = .03–.51). Further, different patterns of prediction emerged as a function of the measurement approach. Adolescent delinquency was a significant predictor of subsequent self-reported child welfare contact, and young adult partner risk was a significant predictor of perpetration of maltreatment as indexed by both official child welfare records and self-reported child welfare contact. In addition, women who were originally assigned to the intervention condition reported perpetrating less maltreatment during young adulthood. Implications for measurement and interventions related to reducing the risk for intergenerational transmission of risk are discussed.